Kansas Family Physicians Perceptions of Parental Vaccination Hesitancy - Mills, Kale; Nilsen, Kari (Kansas Journal of Medicine, 2020)
Introduction. In the past few decades, patients expressing the idea that vaccines are unsafe or unneeded have been experienced increasingly by physicians and other healthcare providers. Discussions with patients regarding their reasons for vaccine refusals are important, as it may provide information that can be utilized in an intervention to increase vaccination rates and combat the spread of diseases that are making a resurgence in the United States. The main objective of this study was to explore the perceptions of family physicians as to why parents in Kansas may be vaccine hesitant.Methods. An electronic survey was distributed to family physicians in the State of Kansas via the University of Kansas School of Medicine-Wichita Family Medicine Research and Data Information Office (FM RADIO). Several aspects of physician perceptions regarding patients’ vaccine hesitancy were measured in this study, including vaccines that are most often refused, reasons for refusing vaccinations, as well as what responses physicians employ when presented with vaccine concerns.Results. The majority of physicians surveyed have experienced vaccine hesitancy or refusal in their practice, and the human papillomavirus (HPV) and flu vaccines were reported to be the primary vaccines refused for children. In addition, physicians reported frequently employing various practices in response to vaccine refusals, including requiring parents to sign a form (40%) and dismissing families from their practice (1.5%). Physician perceptions on the reasons as to why parents/guardians refuse vaccinations also were measured, and the most common response was that parents possess a fear of long-term complications for their children as a result of vaccines (74%). Additionally, the three most commonly refused vaccines were HPV, influenza, and measles, mumps, and rubella.Conclusion. Physicians must not only deal with time constraints that vaccine hesitant discussions require, but also must try and implement discussions or interventions suited to the varying reasons why parents/guardians refuse vaccines to convince parents of their safety. The results suggested that vaccine refusals by parents/guardians seemed to be affecting Kansas family physicians’ clinics in more than one way. This study could be a useful tool to help physicians better understand why vaccine refusals occur and be able to combat unwarranted concerns about vaccines.